Evaluasi Pembelajaran Matematika Berbasis Teknologi Pada Kurikulum Merdeka - Sumarno, Mahmuda; T, Ahmad Yani (Journal of Educational Review and Research, 2024)
The existence of government policy government policy in the form of the implementation of an independent curriculum causes learning in schools to optimize the use of technology. school currently optimizes the use of technology. Mathematics as the main of science and the basis of technological development is very important to learn. important to learn. Mathematics learning that utilizes technology can be implemented through various components, one of which is assessment. Evaluation of mathematics learning carried out in schools still does not indicated the utilization of technology in its application. Lack of references in the implementation of technology-based mathematics learning evaluation makes teachers rarely utilize technology to carry out assessments. Evaluation technology-based mathematics learning evaluation can facilitate teachers in create efficient learning and train students to implement technology in learning. implement technology in learning. This research aims to provide a reference in the form of a description of the meaning, function, objectives, and how to implement technology-based mathematics learning evaluation technology-based mathematics learning evaluation in Merdeka curriculum. The method used in this research is a literature review method with a descriptive qualitative approach. Technology-based mathematics learning evaluation on Merdeka curriculum can be used by utilizing supporting software. Software The software is in the form of an application that can provide feedback, assess directly, and provide reports related to learning achievement and learner development. learners' development. One of the implementations of learning evaluation technology-based mathematics learning evaluation in the Merdeka curriculum can be in the form of utilizing Quizizz application for evaluation based on diagnostic functions, formative functions, and summative functions. formative, and summative functions